Crusading and trading between West and East
1 online resource.
Keywords: "For almost sixty years Professor David Jacoby devoted his research to the economic, social and cultural history of the Eastern Mediterranean and this new collection reflects his impact on the study of the interactions between the Italian city-states, Byzantium, the Latin East and the realm of Islam. Contributors to this volume are prominent scholars from across Medieval Studies and leading historians of the younger generation"--